Characteristics of house calls in Brazil: analysis of PMAQ-AB external evaluation cycles - Luan Henrique Honório Rocha; Ana Graziela Araujo Ribeiro; Vanessa Almeida Silva; Francenilde Silva de Sousa; Erika Barbara Abreu Fonseca Thomaz (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2024)
ABSTRACT Objective: To analyze characteristics of the home visit (HV) in Brazil, 2012 and 2017. Methods: Ecological study, with panel data whose units of analysis were the Primary Health Care teams in Brazil, participants of the 1st and 3rd cycles of the Program to Improve Access and Quality of Primary Care of the Unified Health System. Descriptive, inferential and spatial analyzes (alpha=5%) were performed. Results: There was an increase in the proportion of teams that carried out home visits at a frequency defined based on risk and vulnerability analysis and actively searched for people with respiratory symptoms and women with delayed and altered cytopathological examination. In the heat maps, the Northeast, Southeast and South regions had a higher concentration of teams that carried out the HV and carried out an active search. Conclusion: The maintenance and qualification of HVs must be a priority in Brazil, since there are few countries in the world with such capillarity of health services, reaching the homes of millions of people.